PENGARUH THREAT EMOTION DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN PASTA GIGI PEPSODENT (STUDI KASUS PADA KONSUMEN DI WILAYAH KECAMATAN JAMBU) - Maylesa Dea Marantika; Saryadi Saryadi (Universitas Diponegoro, 2017)
This research is motivated because of the negative pressure that arise in the human being called Threat Emotions or feel threatened. While Trust (Brand Trust) awakened because of the expectation that the other party will act in accordance with the needs and desires of consumers. For that, Pepsodent toothpaste trusted by consumers will be able to overcome the problems of dental health experienced by consumers in the District of Jambu.The purpose of this study was to determine the effect of Threat Emotion and Brand Trust on Purchase Decision of Pepsodent Toothpaste (Case Study on Consumers in Jambu District). This type of research is explanatory, with data collection techniques through kuesione, interview and literature study. The technique of taking respondents using multistage sample technique. Respondents numbered 100 people who are consumers of toothpaste consumers of Pepsodent in the District of Jambu. The analysis technique used is quantitative. Quantitative analysis uses validity test, reliability test, correlation coefficient, coefficient of determination, simple and multiple regression analysis, and significance test (t test and F test).The results of this study indicate that Threat Emotion and Brand Trust have a positive influence on Purchase Decision of Pepsodent Toothpaste (Case Study on Consumers in Jambu District). Variable Brand Trust has the greatest influence that is 0.750 while variable Threat Emotion has the effect of 0.427. Simultaneously (together) the variables of Threat Emotion and Brand Trust have contributed 57.7 percent to the Purchase Decision of Pepsodent Toothpaste.Suggestion that can be given, for pepsodent toothpaste manufactures, should be more aggressive to conduct product introduction progams to consumers about what is given or the benefits of pepsodent thoothpaste more fully for consumers who use it. So that will feel the effect or deeper threath emotion that will increase brand trust that makes purchasing decisions increase.